(untitled) (Scottish Historical and Archaeological Internet Reports, 2001)
A total of 66 fragments of window glass came from a single pit cut into the rubble infill of room 11, the refectory. It is a relatively large collection of Scottish glass which allows for comparison with other Scottish abbeys, most notably the major Augustinian house at Jedburgh in Roxburghshire. Many of the fragments are of grissaile and none appear to be coloured though this could be a feature of poor preservation.